ChemInform Abstract: Triazolbenzo[d]thiazoles: Efficient Synthesis and Biological Evaluation as Neuroprotective Agents. Issue 4 (31st January 2013) - Avila, Belem; Roth, Aaron; Streets, Heather; Dwyer, Donard S.; Kurth, Mark J.
Abstract Two series of title compounds of type (III) and (VII) are prepared utilizing Cu‐catalyzed azide—alkyne click reactions.